2014
DOI: 10.1590/s1984-82502014000300024
|View full text |Cite
|
Sign up to set email alerts
|

Development of O/W emulsions containing Euterpe oleracea extract and evaluation of photoprotective efficacy

Abstract: Euterpe oleracea Mart. is a palm tree popularly known as açai, which is primarily found in northern Brazil. The açai's fruits contain anthocyanins, a class of polyphenols to which antioxidant properties have been attributed. The aim of this work was to develop O/W sunscreens emulsions containing açai glycolic extract (AGE) and to evaluate both their physical stability and photoprotective efficacy. Emulsions containing AGE and sunscreens were formulated using different types and concentrations of polymeric surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…The glycolic extract of açai was used to prepare a sunscreen emulsions (o/w). The resulted cream showed a good protection UV-A and UV-B factor (Daher et al, 2014).…”
Section: Uses Of Açai In Cosmeticsmentioning
confidence: 94%
“…The glycolic extract of açai was used to prepare a sunscreen emulsions (o/w). The resulted cream showed a good protection UV-A and UV-B factor (Daher et al, 2014).…”
Section: Uses Of Açai In Cosmeticsmentioning
confidence: 94%
“…Fotoprotektivni potencijal emulzije tipa ulje u vodi u koju je inkorporirano 5% glikolnog ekstrakta plodova asai palme (INCI: Euterpe Oleracea Fruit Extract) sa organskim UV filterima ispitivan je in vivo i in vitro spektrofotometrijski prema preporukama i vodičima profesionalnog udruženja evropske industrije za ličnu negu Cosmetics Europe [133,134] uz određivanje faktora zaštite od UVB i UVA zračenja, SPF i UVA-PF. Dobijeni rezultati ukazali su da prisustvo ekstrakta ploda asai palme u emulziji koja već sadrži organske UV filtere utiče na povećanje faktora zaštite od UV zračenja (SPF = 25,3 ± 4,5 u odnosu na SPF = 22,5 ± 2,4; UVA-PF = 14,97 ± 0,44 u odnosu na UVA-PF = 13,38 ± 0,52) usled sinergističkog delovanja [135].…”
Section: Biljna Ulja I Ekstrakti Kao Izvori Nefenolnih I Polifenolnihunclassified
“…An açaí extract was investigated by Daher et al . to determine its photoprotective activity in O/W emulsions. In this study, the emulsion containing açaí glycolic extract showed a PF‐UVA of 14.97, a 1.69 SPF/PF‐UVA ratio and a critical wavelength of 378 nm.…”
Section: Plant Compounds In Sunscreensmentioning
confidence: 99%
“…), a native palm of the Amazon region, contains essential nutrients and anthocyanins, which are a class of polyphenols with reported antioxidant properties [74][75][76][77]. An ac ßa ı extract was investigated by Daher et al [78] to determine its photoprotective activity in O/W emulsions. In this study, the emulsion containing ac ßa ı glycolic extract showed a PF-UVA of 14.97, a 1.69 SPF/PF-UVA ratio and a critical wavelength of 378 nm.…”
Section: Plant Compounds In Sunscreensmentioning
confidence: 99%